2018
DOI: 10.1038/nrclinonc.2018.30
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-based cancer risk prediction: rationale, opportunities and challenges

Abstract: The incidence of cancer is continuing to rise and risk-tailored early diagnostic and/or primary prevention strategies are urgently required. The ideal risk-predictive test should: integrate the effects of both genetic and nongenetic factors and aim to capture these effects using an approach that is both biologically stable and technically reproducible; derive a score from easily accessible biological samples that acts as a surrogate for the organ in question; and enable the effectiveness of risk-reducing measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 209 publications
3
118
0
2
Order By: Relevance
“…Around 57 and 43% of endometrial cancers in the United States and the European Union, respectively, are thought to be attributable to overweight and obesity . Obesity can increase risk of endometrial cancer by a variety of mechanisms, including the conversion of androgens to estrogens via aromatase activity enhancing concentrations of endogenous sex hormones, and chronic inflammation mediated by proinflammatory adipokines and hyperinsulinemia, and epigenetic changes among others . Both Types I and II endometrial cancers have been linked to BMI, although the endometrioid subtype seems to be the histology predominantly associated to BMI.…”
Section: High‐risk Populationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Around 57 and 43% of endometrial cancers in the United States and the European Union, respectively, are thought to be attributable to overweight and obesity . Obesity can increase risk of endometrial cancer by a variety of mechanisms, including the conversion of androgens to estrogens via aromatase activity enhancing concentrations of endogenous sex hormones, and chronic inflammation mediated by proinflammatory adipokines and hyperinsulinemia, and epigenetic changes among others . Both Types I and II endometrial cancers have been linked to BMI, although the endometrioid subtype seems to be the histology predominantly associated to BMI.…”
Section: High‐risk Populationsmentioning
confidence: 99%
“…Epigenetic markers have the advantage of being modifiable and they can also be used to monitor response to preventive actions, besides indicating risk of developing cancer. 43 MLH1 and HAND2 methylation are also early events in endometrial carcinogenesis, and occur in AH/EIN and/or endometrial cancer. [43][44][45][46] Furthermore, HAND2 methylation in premalignant endometrial lesions have shown to be less likely to respond to hormonal treatment.…”
Section: Molecular Alterations In Endometrial Precursor Lesionsmentioning
confidence: 99%
See 2 more Smart Citations
“…For other cancer forms, longitudinally followed cohorts with blood samples may be particularly useful. There are indications that even cervical smear biobanks may be useful for the discovery of biomarkers for screening for other cancer forms because epigenetic modifications of DNA occur early in life, affect the risk for multiple cancer forms and can be measured in the DNA of cervical cells (Widschwendter et al, 2018). The concept to systematically link biobanks with cancer registries aiming to establish a study base with blood samples that can be used for longitudinal research on screening has been known for decades (Pukkala et al, 2007) and there are very large cohorts with blood samples established for cancer research broadly, such as the Janus cohort in Norway (Langseth et al, 2017) and the Finnish Maternity Cohort (Lehtinen et al, 2017), or more specifically for breast cancer screening, such as the Karma cohort in Sweden (Gabrielson et al, 2017).…”
Section: Furthering a Research Infrastructure For Biomarker Discoverymentioning
confidence: 99%